2016
DOI: 10.2135/cropsci2016.03.0189
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of SNP Markers Linked to the Stripe Rust Resistance Gene Yr5 in Wheat

Abstract: Stripe rust (Puccinia striiformis Westend f. sp. tritici) is a devastating disease for wheat (Triticum aestivum L.) production worldwide. Yr5 is a race‐specific resistance gene, effective to all races that have been identified in the United States. Therefore, it has been increasingly used for US cultivar development. The goal of this study was to identify and validate single‐nucleotide polymorphism (SNP) markers tightly linked with Yr5, evaluate their usefulness with a diverse set of wheat materials, and disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
(111 reference statements)
1
23
0
1
Order By: Relevance
“…1C). The SNPs IWA6121 and IWA4096 flanking Yr5 are around the 692 to 696 Mb regions ( Supplemental Table S5) (Naruoka et al, 2016). In addition, the saturated genetic map constructed by 90K and GBS SNPs in this study is accurate enough to identify the correct physical locations for genes or QTL and will be a valuable platform for marker-assisted breeding and map-based cloning.…”
Section: Snp Name Kasp Primersmentioning
confidence: 86%
See 3 more Smart Citations
“…1C). The SNPs IWA6121 and IWA4096 flanking Yr5 are around the 692 to 696 Mb regions ( Supplemental Table S5) (Naruoka et al, 2016). In addition, the saturated genetic map constructed by 90K and GBS SNPs in this study is accurate enough to identify the correct physical locations for genes or QTL and will be a valuable platform for marker-assisted breeding and map-based cloning.…”
Section: Snp Name Kasp Primersmentioning
confidence: 86%
“…Yr44, first identified in cultivar Zak, was mapped ?42 cM away from Yr5 using 300 F 2 plants from the cross of Zak/Yr5 (Sui et al, 2009). Naruoka et al (2016) reported that IWA6121 and IWA4096 at 696.7 Mb of 2B (Fig. 1C) were identified as flanking markers for Yr5.…”
Section: Genetic Basis Of Stripe Rust Resistancementioning
confidence: 96%
See 2 more Smart Citations
“…album accession [49]. It is mapped on chromosome 2BL [50][51][52][53][54] and is effective against all Pst races identified in the United States [55] although Wellings and McIntosh [56] reported virulence from two Australian Pst isolates. The fact that Yr5 marker T_LYr5 amplified the same allele in both positive and negative controls makes the detection ambiguous.…”
Section: Kasp Assay Based Screening For Known Yr Genesmentioning
confidence: 99%